(3HMhK LGeYjI aj GdUMGaI h GdEYdGe (B/s - (3hgHj, SMQ eMeOs ((3GdbGgQI (B:s (3OGQ GdaLQ ddfTQ h GdJhRjY ,s, 2004)
(3jfbSe Edi KdGKI aUhd GdaUd GdChd jMJhi Ydi OQGSI JMdjdjI dQSGFd GdeLGSJjQ h GdOcJhQGg GdeefhMI ef bSe GdEYdGe HcdjI GdGOGH HShgGL ef GcJhHQ(B1977 (3Gdi eGjh (B2002s
Keywords: (3GdEYdGes; (3GdUMGaIs